The Weeds in Sunflower Crops when Grown in Arid Conditions of The Steppe of Ukraine - Igor Aksyonov (Turkish Journal of Agriculture: Food Science and Technology)
In the arid conditions of the Steppe of Ukraine, the species composition of weeds characteristic of this soil-climatic zone develops. The correctly chosen method of basic soil tillage determines the effectiveness of weed suppression while simultaneously improving the growing conditions for sunflower varieties and hybrids. The purpose of the study was to identify the species composition of weeds in the steppe zone and establish the effectiveness the methods of basic tillage of soil in the technology of growing sunflower hybrids aimed at suppressing weeds and reducing the quantity of weeds in agrocenoses. Research has established that weeds of sunflower agrophytocenoses are represented by 78 species that belong to 2 classes, 18 orders, 27 families, 62 genera. In the agrophytocenosis of sunflower, the largest number of 93.5-96.3% is represented by dicotyledonous weeds (Magnoliopsida). The species composition is dominated by weeds of the Compositae family (Asteraceae) of the dicotyledonous class (Magnoliopsida), which leads to a significant decrease in the yield level. According to the species composition, 3 groups of weeds of the Asteraceae family (Asteraceae) were identified, of which 1 group of weeds is the most harmful and leads to the formation of a minimum yield of sunflower hybrids Yason and Daryi of 1.77-1.79 t/ha. The use of non-moldboard tillage leads to a percentage increase in the share of air dry mass of weeds of the Asteraceae family by 11.1-13.1%, while reducing the yield of sunflower hybrids by 0.13-0.21 t/ha. Thus, with the established species composition of weeds and the quantity of weeds, the use of plowing in sunflower cultivation technology makes it possible to form a maximum yield of 2.07-2.24 t/ha, providing more effective weed suppression in sunflower agrophytocenoses with a minimum percentage of air-dry mass of weeds of the Asteraceae family to the total number of weeds of 21.1-24.1%.